2022
DOI: 10.1002/ca.23875
|View full text |Cite
|
Sign up to set email alerts
|

Full color 3D printing of anatomical models

Abstract: We propose an effective method for manufacturing human anatomical specimens in response to the shortage of cadaver specimens and the poor simulation results of anatomical specimen substitutes. Digital human data with high precision were used to create digital models and corresponding mapped textures. Different materials were chosen to print the digital models with full-color and multimaterial 3D-printing technology based on the histological characteristics of the anatomical structures.Anatomy experts and surge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 34 publications
0
15
0
Order By: Relevance
“…Several studies have reported the results of using 3D printing in the education of students and residents. A recent study reported on 3D printing models with a variety of colors to replace the anatomy education with cadaveres 16 , 17 , and 3D-printed liver was reported to be more efficient than a traditional atlas in anatomy education 18 . In education of pathologic models of aortic aneurysm and cancers, 3D printing was useful for surgical education from the survey results 19 .…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported the results of using 3D printing in the education of students and residents. A recent study reported on 3D printing models with a variety of colors to replace the anatomy education with cadaveres 16 , 17 , and 3D-printed liver was reported to be more efficient than a traditional atlas in anatomy education 18 . In education of pathologic models of aortic aneurysm and cancers, 3D printing was useful for surgical education from the survey results 19 .…”
Section: Discussionmentioning
confidence: 99%
“…The segmentation data were obtained by manually delineating the boundaries and tissue structures in Photoshop software. An improved Marching Cubes algorithm was then used to reconstruct the 3D digital models [ 10 ]. The segmentation data were repeatedly modified and validated, ensuring their accuracy.…”
Section: Methodsmentioning
confidence: 99%
“…The pterygopalatine fossa is a complex anatomical region; its components and their relations are usually difficult to define and visualize. Although previous reviews have reported the process of integrating medical images with printed models, 25 most studies have focused on producing the entire skull model because of the challenge of segmenting and rebuilding the skull 26,27 . Only large and clearly distinct organs and structures can be completely segmented since manually delineating each cross‐section of a structure is time intensive and technician dependent.…”
Section: Introductionmentioning
confidence: 99%